Influence and Traces of Buddhism on Traditional Beliefs of the Kyrgyz People - Nursultan Abdimitalip Uulu; Kayrat Belek; Anarbek Mokeev (Belleten)
While Shamanism predominantly shaped the spiritual life of the Ancient Türks, Buddhism, as the first religion to spread among them, also exerted a significant influence in later periods. Although Buddhism waned among the ancient Türks and the Kyrgyz, it left traces within the boundaries of Turkestan, eventually fading among the contemporary Kyrgyz. The Buddhist inscriptions discovered in the Tian-Shan region and the beliefs associated with Buddhism in Kyrgyz history have been relatively understudied until recently. The introduction provides a brief history of Buddhism’s expansion into Central Asia. Based on the first-hand sources, its dissemination among the Türk and Uyghur States and the information about the influence of this religion on other communities and the Kyrgyz were examined through comparative research. The first section explores Buddhism’s decline following Islam’s spread in Turkestan, as documented in Dīwān Lughāt al-Turk by Mahmud Kashgari. The second section examines the development of Buddhism in Central Asia and the Junghars’ (Qalmuq) aspirations to conquer Turkestan. In conclusion, this article offers a comparative analysis of written sources concerning Kyrgyz history, tracing the key phases of Buddhism’s influence on Kyrgyz people and Kyrgyzstan. Lastly, the study delves into the etymological origins of terms like “Manas”, “qut”, “chatyr”, “cherik” and “eshtek” suggesting their Sanskrit roots through Buddhism in the culture and spiritual beliefs of Kyrgyz, shedding light on the preservation of ancient beliefs of the Kyrgyz’s.